Projetos de Formação Contínua de Educadores para uma Prática Crítica - Magalhães, Maria Cecília Camargo (The ESPecialist, 2012)
This paper aims at discussing the theoretical frame of research projects conducted in schools as a way to create contexts in which teachers and/or coordinators learn how to become investigators of their own action while interacting with colleagues and/or a researcher. Based on critical practice, and on social historical research, it discusses the necessity of research methods that might introduce self-reflectivity and questionning into school settings.